Electro-optically active ring devices for CMOS-compatible optoelectronics - Li, Fuqiang. (2013)
Electro-optic modulators are one of the most crucial components in optoelectronic integration. We proposed a novel modulator based on the hybrid LiNbO3-on-SOI (silicon-on-insulator) platform. Travelling wave Nested Ring Mach-Zehnder Interferometer (NR-MZI) design is applied for high modulation efficiency and broad bandwidth. The waveguide cross section, nested ring layout and electrode structure were optimized for the best performance of the modulator. In detail, high modulation efficiency, low propagation loss, maximum extinction ratio and step edge on the spectrum, and fast modulation speed and broad modulation bandwidth are the key characteristics for performance. The modulator with a 3 dB bandwidth over 150 GHz could be achieved using the optimized structure. The results demonstrated in this thesis provide a theoretical foundation to the mass production of optical modulators, revolutionizing the optical communication with substantial cost reduction.